Carbonic anhydrase inhibitor attenuates ischemia-reperfusion induced acute lung injury - Lan, Chou-Chin (PLoS One, 2017)
Ischemia-reperfusion (IR)-induced acute lung injury (ALI) is implicated in several clinical conditions including lung transplantation, cardiopulmonary bypass surgery, re-expansion of collapsed lung from pneumothorax or pleural effusion and etc. IR-induced ALI remains a challenge in the current treatment. Carbonic anhydrase has important physiological function and influences on transport of CO(2). Some investigators suggest that CO(2) influences lung injury. Therefore, carbonic anhydrase should have the role in ALI. This study was undertaken to define the effect of a carbonic anhydrase inhibitor, acetazolamide (AZA), in IR-induced ALI, that was conducted in a rat model of isolated-perfused lung with 30 minutes of ischemia and 90 minutes of reperfusion. The animals were divided into six groups (n = 6 per group): sham, sham + AZA 200 mg/kg body weight (BW), IR, IR + AZA 100 mg/kg BW, IR + AZA 200 mg/kg BW and IR+ AZA 400 mg/kg BW. IR caused significant pulmonary micro-vascular hyper-permeability, pulmonary edema, pulmonary hypertension, neutrophilic sequestration, and an increase in the expression of pro-inflammatory cytokines. Increases in carbonic anhydrase expression and perfusate pCO(2) levels were noted, while decreased Na-K-ATPase expression was noted after IR. Administration of 200mg/kg BW and 400mg/kg BW AZA significantly suppressed the expression of pro-inflammatory cytokines (TNF-α, IL-1, IL-6 and IL-17) and attenuated IR-induced lung injury, represented by decreases in pulmonary hyper-permeability, pulmonary edema, pulmonary hypertension and neutrophilic sequestration. AZA attenuated IR-induced lung injury, associated with decreases in carbonic anhydrase expression and pCO(2) levels, as well as restoration of Na-K-ATPase expression.